2021
DOI: 10.1051/e3sconf/202128203023
|View full text |Cite
|
Sign up to set email alerts
|

Rumen bacterial community, indicators of reproduction and milk productivity at different levels of protein concentrate in the diets of dairy cows

Abstract: The use of new sources of by-pass protein in the cow diets to optimize milk production and herd reproduction performance indicators in modern economic conditions is relevant. The article presents data on the use of a protein concentrate containing plant and animal components and its effect on the quality of the milk obtained, the state of the rumen bacterial community and reproduction indicators. The use of protein concentrate of both 1.0 kg and 1.5 kg/head/day contributed to improving the quality and increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Analysis of the rumen content showed that the number of Bacteroidetes in cows of groups (1.0 and 1.5 kg/day) receiving protein concentrate in their diets was reduced by 1.5% and 2.9%. There were no significant differences between the control group and the groups receiving PCAM supplements and in most of the rumen microbiota, with the exception of pathogenic microorganisms such as Peptococcus and Fusobacteria; a significant decrease was noted between the control group and the groups receiving PCAM supplements [31,34,35].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Analysis of the rumen content showed that the number of Bacteroidetes in cows of groups (1.0 and 1.5 kg/day) receiving protein concentrate in their diets was reduced by 1.5% and 2.9%. There were no significant differences between the control group and the groups receiving PCAM supplements and in most of the rumen microbiota, with the exception of pathogenic microorganisms such as Peptococcus and Fusobacteria; a significant decrease was noted between the control group and the groups receiving PCAM supplements [31,34,35].…”
Section: Introductionmentioning
confidence: 78%
“…The basis for increasing the productivity of livestock is to meet the needs of the body, firstly, in the optimal intake of nutrients from the diet, and secondly, their effective decomposition to monomers in the gastrointestinal tract and use for the needs of the body and productivity [47,53,54]. Rations containing animal proteins have a more complete digestible protein, because in ruminants, more precisely in rumen microorganisms, there are no enzymes capable of breaking them down to amino acids and subsequently to amino acids [35].…”
Section: The Rationmentioning
confidence: 99%
See 2 more Smart Citations